Impact of Artificial Intelligence and Cyber Security as Advanced Technologies on Bitcoin Industries - Deepak, A.; William, P.; Dubey, Rajat; Sachdeva, Shilpa; Vinotha, C.; Masand, Sunny; Shrivastava, Anurag (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This review article investigates the relationship between Bitcoin and artificial intelligence (AI), as well as any potential consequences on the Bitcoin market. Also included are any implications for the future of the cryptocurrency. The literature review focuses on the existing research on the relationships between artificial intelligence technology and Bitcoin, and it provides an overview of both of these businesses. This research investigates the potential impacts that AI might have on the Bitcoin industry, including improved user experiences, better levels of transactional security, and enhanced operational efficiencies. The paper also analyses the challenges that occur from applying AI to the Bitcoin industry in terms of the rules and regulations, data security and privacy, and trust that exist in the sector. In recent years, cryptocurrencies have emerged as a dominant form of digital money, and the financial system itself has evolved into an increasingly important component in this space. In order to reduce the amount of risk that is associated with investing, certain approaches that are based on artificial intelligence are required to predict price and trend, as well as to design portfolios and identify fraudulent activity. Along with recent research on AI-based strategies for cryptocurrencies, the most well-known cryptocurrency, Bitcoin, is explored in this article. The articles that were determined to be the most relevant were assessed, and this page addresses the bulk of those publications. This contains research on Bitcoin and other cryptocurrencies, as well as techniques of machine learning such as SVM, ANN, LSTM, and GRU.